Pengembangan Sistem Informasi Sosial Ekonomi Untuk Menunjang Perencanaan Wilayah Tingkat Provinsi (Uji Coba di Provinsi Lampung) - Nurjanah, Nurjanah; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Development activities demand land use and spatial planning which are supported by a geographically based physical and socio-economic information system. The availability of fast, accurate and current data has been a fundamental challenge in regional planning. Currently, data needed for urban and regional development planning has not been fully available at the basic data providing institution. Discrepancy of definitions between the data provider and user (the regional planners) are not uncommon. One solution is to establish a specific spatial information system containing the data needed by the planners. The study aims to develop a model of social-economic information system to support regional planning activity at the provincial level. The system contains demographic and economic data and information, which will be used in the regional planning process by using Arcview software. The sistem should assist regional planners by providing fast information in the spatial dimension. The study concluded that the now established system has given simplicity in work with added aesthetical value. The system helps both spatial and numerical analysis by integrating both data system, allowing policy makers and development actors to easily make a decision based on spatial dimension.